Keynes: updated or outdated? - Marshall, Natalie J. (Lexington, Mass.: D.C. Heath and Company, 1970)
The book is divided into two parts. I. The Validity of Keynesian Theory. II. The Validity of Keynesian Policy.
rpm 08/11/2017
Loans
Keywords: Keynesian economics